Totally Between Subjectivity and Discourse. Exploring the Pragmatic Side of Intensification. (7th March 2018) - Beltrama, Andrea
Abstract: In American English, the intensifier totally presents a pragmatic use, in which it strengthens the speaker's commitment towards the utterance (e.g. 'The Bulls will totally make the playoffs'). This use has received considerably less attention than the canonical lexical contribution of the adverb (e.g. 'the glass is totally full'). First, I rely on three acceptability studies to show that pragmatic totally is used only in discourse moves that allow for the possibility of not adding p to the Common Ground of the conversation—that is, subjective, outlandish and responsive assertions. Second, I propose that totally flags speaker's meta-conversational belief that every continuation of the exchange should involve the addition of p, framing the analysis within Farkas & Bruce (2010) 's discourse model. The proposal allows us to account in a unified way for the different effects that pragmatic totally contributes, highlighting the intensifier as a window into how declarative sentences with different kinds of content—subjective, objective, outlandish—structure the conversation.